Behavioural ecology of predation and foraging in Eriopis connexa (Germar, 1824) (Coleoptera, Coccinellidae): experimentation and modelling - Maciel, Anna Mara Ferreira (2026)
The family Aphididae comprises insects commonly known as aphids, which cause both direct and indirect damage to the crops they infest, resulting in significant reductions in agricultural productivity. Among the available strategies for managing these pests, biological control through the use of natural enemies stands out as a sustainable and ecologically sound alternative. In this context, coccinellids represent a highly relevant group, as they include numerous generalist predatory species capable of exploiting different prey associated with a wide range of agricultural crops. The ladybird Eriopis connexa (Germar, 1824) is recognized for its high voracity when feeding on aphids and its wide distribution across South American agroecosystems. However, recommending the use of natural enemies in integrated pest management programmes requires a detailed understanding of the processes governing predatorprey population dynamics. Chapter 1 provides the general framework of the thesis, addressing the economic and ecological importance of the aphid species studied, the principles of foraging behaviour in generalist predators, multitrophic interactions including intraguild predation, and the role of mathematical modelling as a tool for investigating predatorprey dynamics. In Chapter 2, the predatory behaviour and functional response of E. connexa towards Myzus persicae (Sulzer, 1776) and Aphis gossypii Glover, 1877 are investigated experimentally under different ecological contexts. The results indicate that the ladybird consumes early instars more intensively than later developmental stages and adjusts its predation patterns according to the relative abundance of prey, demonstrating context-dependent foraging decisions. In Chapter 3, a stage-structured mathematical model was developed to investigate the population dynamics of E. connexa interacting with both aphid species, incorporating prey relative abundance and the presence of an aphid parasitoid. Simulations revealed that intraguild predation can play a central role in regulating species coexistence and system stability, promoting dynamic equilibria that depend on the relative intensities of predation and parasitism. Finally, Chapter 4 explores, through mathematical modelling, the effects of insecticide application on predatorprey dynamics, considering susceptible and resistant populations of E. connexa. The results show that differences in mortality, attack rate, and handling time between these populations strongly influence predatory efficiency and aphid control. In addition, insecticide application induced population fluctuations that may compromise biological control when not properly integrated into pest management strategies. Taken together, the results of this thesis highlight the importance of combining experimental approaches and mathematical modelling to improve our understanding of predatorprey dynamics and to optimise the use of natural enemies in integrated pest management programmes.